Ureolytic microbial community is modulated by fertilization regimes and particle-size fractions in a Black soil of Northeastern China. (January 2018) - Wang, Li; Luo, Xuesong; Liao, Hao; Chen, Wenli; Wei, Dan; Cai, Peng; Huang, Qiaoyun
Abstract: Ureolytic microbes are important contributors to N cycling in soil. The distribution of the ureolytic microbial community in different particle-size fractions (2000-250, 250-53, <53 μm) was determined by high-throughput sequencing and q-PCR analyses in 35-year-old fertilization experiment on Black soil. Fertilizer treatments included an unfertilized control, chemical NPK fertilizer, horse manure and NPK fertilizer plus horse manure. Each fertilizer treatment harbored a structurally distinct ureolytic microbial community. The dominant ureolytic microbes were putatively associated with Rhizobiales, Burkholderiales, Rhodocyclales, Pasteurellales, Pseudomonadales, Oceanospirillales, Myxococcales, Micrococcales and Corynebacteriale species. The OTUs associated with the same fertilizer treatment or particle-size fraction were scattered across the phylogenetic tree, and only sequences related to Rhizobiales showed a similar increase in response to manure application. The abundances of ureC genes ranged from 1.5 ± 0.38 × 10 7 to 9.1 ± 0.91 × 10 7 g −1 dry soil and accounted for 0.4% to 2.9% of the total bacteria (represented by the copy numbers of the 16SrRNA genes). Significantly lower ureC gene abundance was observed in manure-amended soil, whereas the macro- and microaggregates had higher ureC gene abundances than the silt + clay fraction. The abundance of ureolytic microorganisms was significantly correlated with soil NH4, total nitrogen (TN) and carbon (TC) concentrations. This indicates that variation in ureolytic microbial communities was associated with soil nutrient levels. Urease activities in the particle-size fractions were as follows: microaggregate > macroaggregate > silt + clay. Additionally, urease activities were correlated with the TN, TC and soil organic carbon (SOC) concentrations, but not with the abundances of the ureC genes. In summary, our study first revealed the heterogeneity in the ureolytic microbial communities and activities across different particle-size fractions under long-term fertilization. Microaggregates seems to be a "hotspot" for nutrients, ureolytic microorganisms and urease activity. Highlights: Ureolytic microbial community was investigated with high throughput sequencing. Manure application is the major driver of the ureolytic microbial community. The three particle-size fractions harbor distinct ureolytic microbial communities. Microaggregate is "hotspot" for ureolytic community and urease activity. Urease activity was not correlated with ureC genes copies in Black soil.